Larrinaga, Carlos y Strangio, Donatella (eds.): The Development of the Hotel and Tourism Industry in the Twentieth Century Comparative Perspectives from Western Europe, 1900-1970. Londres, Palgrave-Macmillan, 2023. 222 pp. - Barral Martínez, Margarita (Cuadernos de Historia Contemporánea, 2025)
Review of the booj Larrinaga, Carlos y Strangio, Donatella, (Eds.): The Development of the Hotel and Tourism Industry in the Twentieth Century Comparative Perspectives from Western Europe, 1900–1970. Londres, Palgrave-Macmillan, 2023. 222 pp